Brokerage fee, ownership expropriation and earnings management of Malaysian property companies. Issue 4 (27th July 2018) - Ung, Lik Jing; Brahmana, Rayenda Khresna; Puah, Chin-Hong
Abstract : Purpose: The purpose of this paper is to investigate whether real estate companies manipulate their earnings through the brokerage fee across ownership expropriation or not. Design/methodology/approach: This study considers Kuala Lumpur Stock Exchange listed real estate firms to investigate how the brokerage fee in the real estate industry might affect the earnings management of firms across its ownership expropriation. Using annual report data, the authors investigate the associations over a panel for the period 2008−2012. Robust panel regression is used to divulge the probability values with reference by probit regression. Findings: Overall, the results show that high brokerage fees would drive more events of earnings management and that, generally, the ownership concentration among Malaysian real estate firms significantly affects the earnings management of the firms. Practical implications: This study shows that firm profitability and brokerage fees enhance the probability of firm's earnings management. A low brokerage fee would reflect low revenue to the company. Therefore, management would opt to manipulate earnings in order to overstate earnings, which garners more interest from investors. Originality/value: Real estate values in Malaysia have climbed steadily over the years due to a combination of reasons giving companies a higher brokerage fee. Earnings management has become a big issue for property investors. The study demonstrates the relationship between earnings management and brokerage fee across ownership expropriation which can be considered by shareholders in their own strategic planning and investors in their own investing.